Effectiveness of the Implementation of the Diploma Withholding Prohibition Policy in Yogyakarta City - Muhammad Rifki Taufikurrahman; R. Widodo Triputro (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2026)
This study analyzes the effectiveness of implementing the policy prohibiting diploma withholding in senior high schools in Yogyakarta City, based on Daerah Istimewa Yogyakarta Regional Regulation No. 10/2013. Using a qualitative descriptive approach with data from interviews, observation, and documentation, the research applies Edward III’s implementation model focusing on communication and disposition variables. Results show that while transmission of policy information is effective, clarity and consistency are not due to multi-interpretation among private school principals, unclear sanction actors, and differential treatment between public and private schools. Private school principals exhibit ambivalent dispositions, normatively supportive but substantively resistant, driven by financial dependence on tuition, different institutional status, and unclear sanction mechanisms. Consequently, diploma withholding persists through pseudo-compliance strategies, leaving hundreds of diplomas unpaid and unclaimed. The study concludes that policy implementation is ineffective and recommends issuing derivative regulations, consistent enforcement, and alternative financial mechanisms to protect students’ rights without undermining private school viability.